FORMING THE ABILITY TO STRUCTURE INFORMATION TECHNOLOGY (Conferencea, 2023)
Thus, all this predetermines the need to pay serious attention to the formation of skills necessary for effective work with hypermedia in the process of teaching elementary school students and to the creation of an array of information when building hypertext or hypermedia. The analysis of methodological resources and textbooks reliably shows that at present, insufficient attention is paid to the formation of effective methods of working with hypermedia in primary classes. As mentioned above, primary school students should be given assignments on structuring information resulting in hypertext or hypermedia.